ANALISIS KELAYAKAN FINANSIAL PENGOPERASIAN BUS TRANS SARBAGITA KORIDOR VI - Budiartha, I Nyoman; Anggarini, Putu Asih; Agistini, Eka Tamar; Arishandi, Nyoman Gery; Lestari, Dyah Ayu (FSTPT Indonesia, 2015)
The study about the arrangement of transportation in Bali especially arrangement of public transportation has been implemented since year 1990, even though most of it still not well implemented. If short-term financial factor become the main consideration, then mass transportation system in Bali will never be built. Mass transportation system need to be done by considering the economic benefit wholly so that public transportation could perform well, such as government subsidies. The purpose of this study is to analyze the financial feasibility of Sarbagita bus Corridor VI that is planned to serve route: Mengwi terminal – Puspem Badung – Ubung terminal – City, Round-Trip with 30 fleets and 24 stops. Data used in this study is secondary data with estimation of 1,620 passengers per day with government rate Rp. 3,500. The outcome from this study shows that Trans Sarbagita bus corridor VI is not feasible, Vehicle Operating Costs (BOK) per year is Rp. 927,308,322,- for one unit and Rp. 24,190,651,895 per year for the entire fleet. So it need government subsidies in the amount of Rp. 35,894,340 per day.